On the evolutionary origins of differences in sexual preferences - Ryabko, Daniil; Reznikova, Zhanna (Frontiers in Psychology, 2015)
A novel explanation of the evolutionary process leading to the appearance of differences in sexual preferences is proposed. The explanation is fully general: it is not specific to any particular type of sexual preferences, nor to any species or population. It shows how different sexual preferences can appear in any large group-living population in which sexual selection is sufficiently strong in each sex. The main idea is that the lack of interest toward a member of the opposite sex may be interpreted as a signal of popularity, and thus of reproductive success. It is then boosted by the Fisher runaway process far beyond the point where it becomes costly, resulting in a generalized trait—lack of interest toward the opposite sex. If the interest diverts toward other targets then different sexual preferences emerge. This hypothesis is placed into the context of other works on different sexual preferences in animals; supporting evidence from the literature is reviewed and additional research needed to confirm or refute the hypothesis in any given species is outlined.